Skating on Thin Ice: Hypothermia and Near-Drowning Simulation - Luan Lawson; Leigh Patterson (Association of American Medical Colleges, 2013)
Abstract This simulation case, intended for medical students and residents in emergency medicine, features an 18-year-old male who presents to the emergency department after falling through thin ice on a pond. The patient was initially coughing and choking, but became combative and submerged just prior to being extracted by emergency medical services. The patient is bradycardic, hypotensive, and hypoxic on arrival to the emergency department. This simulation was developed to specifically focus on the environmental topics of hypothermia and drowning incidents included in the national curriculum for fourth-year medical students defined by the Clerkship Directors in Emergency Medicine, a national organization representing undergraduate medical education in emergency medicine. Learners will need to demonstrate the initial evaluation of the hypothermic, near-drowning victim, including consideration of potential traumatic injury. This simulation case provides an opportunity for medical students and residents to utilize experiential learning to increase their knowledge and retention about near-drowning and hypothermia. Exposure to these environmental emergencies may be inadequate depending on time of year and geographical location. Simulation provides a safe environment to demonstrate management of the hypothermic patient with altered mental status. We have utilized this case with at least three cohorts of students rotating on a required emergency medicine rotation and it has been well-received by students and faculty. We found that our students had little exposure to environmental emergencies in their undergraduate medical education; this case was developed to provide them with the opportunity to care for these types of patients in a simulated environment.